DETERMINATION OF TRAINING COMPETENCE, CHARACTERISTICS OF INDIVIDUALS ON EMPLOYEE’S SATISFACTION THROUGH WORK ACHIEVEMENT IN UPTD PUSKESMAS SEI LEKOP BINTAN DISTRICT - Kurniani, Wiwik; Wibisono, Chablullah; Indrayani, Indrayani (Universitas Batam, 2019)
Sei Lekop Health Center is an overview of the health situation in the UPTD of the Sei Lekop Health Center which is published once a year, in this profile contains various data about health, which includes health status data, health efforts and health resources. The health profile also provides other supporting data related to health such as population data, socio-economic data, environmental data and other data. Data is analyzed by simple analysis and displayed in the form of tables, maps and graphs. In this study the population of researchers amounted to 102 people using the Slovin formula, the sample size of this study from the total population taken by researchers was 102 people and using an error rate of 5%, the number of responses was obtained by 81 people.In the table above the results of the influence of X1, X2 and X3 on X4 (e1) are equal to 0.467, which means that the effect of X1, X2 and X3 on X4 is 46.70%. Then, the effect of X1, X3 and X4 on Y is 0.607, which means that the influence of X1, X3 and X4 on Y is 66.80%.